Temporal changes in headwater streams macroinvertebrate assemblages during the snowmelt season in northeast china - Gao, Yufu; Rong, Liping; Cao, Lina; Li, Kun; Lin, Chenlu; Zhang, Zhenxing; Xiang, Hongyong; Yang, Haijun (Frontiers in Environmental Science, 2022)
Mid-latitude areas such as Northeast China are predicted to have warmer temperature according to IPCC sixth which may influence the duration of the snowmelt season. What remains unknown, however, is how annual snowmelt can influence the biodiversity of macroinvertebrate communities, especially in headwater streams in Northeast China. Here, we investigated the temporal changes (before, during, and after the snowmelt period) of macroinvertebrate communities and stream physicochemical characteristics in five headwater streams in Northeast China. We found that: (1) Macroinvertebrate taxa richness, density, Shannon diversity index, and functional diversity were lower in the melting period than in the other two periods, while biomass and percentage of dominant species were significantly higher in this period; (2) As to functional traits, “erosional”, “strong swimming ability”, “some attachment”, “streamlined shape” and “large size at maturity” traits of the macroinvertebrates taxa were significantly higher in the melting period than in the other two periods; and (3) Redundancy analysis (RDA) and multiple linear regression model found that temperature, turbidity, and velocity were key environmental factors affecting the functional traits of macroinvertebrates during the whole snowmelt process. This study could provide crucial data to support biodiversity conservation and ecosystem restoration of freshwater ecosystems in mid-to high-latitude and alpine areas.